Establishing Cash-Waqf Model for Infrastructure Funding: The Analytic Network Process Study - Resi Ariyasa Qadri; Etty Murwaningsari (International Journal of Emerging Issues in Islamic Studies, 2023)
This research aims to build a cash waqf governance framework that incorporates blended finance to develop the infrastructure in Nusantara, which is the proposed future capital city of Indonesia. Data was collected through a combination of interviews with eight informants and a survey administered to thirty respondents. The acquired data was analyzed using a mixed method that included the thematic evaluation and the analytic network process. The present study posits that the utilization of cash waqf, as a form of innovative financing mandated by the government, holds potential for the development of health infrastructure in the newly established capital of the nation. The findings of this study have significant implications for the development of policies aimed at adopting the blended finance governance structure required by the government.